External evaluation of the CGIAR Research Program on Dryland Systems - Merrey, Douglas J.; McLeod, R.; Szonyi, J. (International Center for Agricultural Research in the Dry Areas, 2015)
The evaluation of CRP on Dryland Systems was organized around five basic questions, as follows: